DYNAMICS OF INFLATION DETERMINANTS UNDER DUAL MONETARY SYSTEMS: EMPIRICAL EVIDENCES FROM INDONESIA AND MALAYSIA - Imamuddin Yuliadi; Dimas Kusuma (Jurnal Ekonomi dan Bisnis Islam | Journal of Islamic Economics and Business, 2016)
Achieving monetary stability is a primary goal promoted by monetary authority, including through reaching low and stable the rate of inflation. Indonesia and Malaysia are the two countries which have been implementing dual monetary system where conventional and Islamic system running side by side. Due to inflation is always a monetary phenomena, it is interesting to look at some determinants which generate the rate of inflation. The paper attempts to investigate which variables, either individually or accumulately, form the inflation in the both countries. Subsequently, which system is more stable in terms of generating inflation rate in both countries?. The paper employs several monetary variables which proxy of conventional and Islamic group spanning from January 2012 till April 2015. By using vector autoregressive (VAR) approach, the results reveal that inflation generating under conventional system is unstable compared to Islamic system due to an inherent instability of interest rate and fractional reserve banking in both countries. Moreover, the Islamic monetary system can reduce the generated inflation in both countries around 25-50% if was practically implemented. Therefore, continous effort in terms of establishing institutional and instrumental arrangements should be gradually developed to further accomodate and enhance the effectiveness of monetary policy particularly in curbing inflation rate under dual monetary systems.